Archaeological charcoal as a window on palaeovegetation and wood-use during the Middle Stone Age at Sibudu Cave - Allott, L. F. (Southern African Humanities, 2021)
Analysis of charcoal from Middle Stone Age layers in Sibudu Cave shows evidence for environmental change and wood selection during the Last Glacial. Layers analysed encompass the end of the cold stadial, Oxygen Isotope Stage (OIS) 4, and the warmer interstadial, OIS 3. Layers are grouped into > 60 ka, ~60 ka, ~50 ka and ~37 ka assemblages. Pre-60 ka layers within the Howiesons Poort (HP) occupations are dominated by evergreen forest taxa, including Podocarpus spp., Buxus sp., Brachylaena sp.,Sapium/Spirostachys and Ptaeroxylon obliquum. Kirkia sp. suggests that a warm, woodland savanna habitat grew beyond the forest vegetation. At ~60 ka there are taxa from evergreen, riverine forest communities, including Erica spp., Leucosidea sericea and Rapanea melanophloeos. Some of the taxa in these layers suggest a shift in vegetation, possibly related to the marine regression of the Last Glacial. A lowered sea-level and slightly cooler climates in South Africa may have enabled taxa currently found farther inland in the mountain foothills to grow closer to the rock shelter than at present. By ~50 ka, fewer evergreen forest components and more bushveld taxa, which are common in northern, drier regions of South Africa, are present.